2012
DOI: 10.1080/00071668.2012.665435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented plant product on growth performance, some blood variables, carcase characteristics, and intestinal histology in broilers

Abstract: 1. Fermented plant product (FPP) is a natural fermented food which is produced from a mixture of fermented fruit and vegetables, and rice bran (1:9). 2. To investigate the effects of FPP on growth performance, some blood variables, carcase characteristics and intestinal histology were determined in 192 broilers. They were divided into 4 groups, with 4 replicates of 12 chicks each; the chicks were provided ad libitum access to a diet consisting of 0, 0·5, 2·0 and 4·0% dietary FPP. 3. The crude protein and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…It was previously reported that organ weight is affected by dietary probiotics supplementation (Awad et al, 2009). However, Lokaewmanee et al (2012) reported that weight of organs has no difference between in group of dietary fermented plant products supplementation and in control group, except for total visceral weights on poultry. In this study, likewise, weight of organs had no difference between in the control and in all treatment groups.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It was previously reported that organ weight is affected by dietary probiotics supplementation (Awad et al, 2009). However, Lokaewmanee et al (2012) reported that weight of organs has no difference between in group of dietary fermented plant products supplementation and in control group, except for total visceral weights on poultry. In this study, likewise, weight of organs had no difference between in the control and in all treatment groups.…”
Section: Resultsmentioning
confidence: 92%
“…Likewise, it was reported that supplementation of FBS to broilers does not affect at blood composition (Lokaewmanee et al, 2012). As well, fed seaweed extract was reported to decrease oxidative stress such as GOT, GPT concentration on animals (Kang et al, 2008).…”
Section: Resultsmentioning
confidence: 98%
“…However, effects of other feed additives, such as garlic, oregano, cinnamon, pepper, thyme and fermented plant products (rice bran and fermented fruit and vegetables) on intestinal histology were observed (García et al, 2007;Abdullah et al, 2010;Lokaewmanee et al, 2012;Giannenas et al, 2014). In fact, more research is need to determine if RP as a feed additive causes gross morphometric changes in the digestive system, particularly on weight, villus density, and on the enterocytes (Applegate et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to AGPs, certain feed additives and functional feedstuffs have commonly been included in poultry diets to enhance the growth rate of broiler chicks, including probiotics, antioxidants, and fermented feed (Lokaewmanee et al, 2012;Sugiharto, 2016). Besides being used separately, AGPs and other feed additives may be used simultaneously to improve the weight gain and feed efficiency of animals.…”
Section: Introductionmentioning
confidence: 99%